2020
DOI: 10.1007/s42452-020-2330-2
|View full text |Cite
|
Sign up to set email alerts
|

Friction stir process: a green fabrication technique for surface composites—a review paper

Abstract: In many applications, surface properties of materials or components are more important than the entire volume material properties. The hardness, wear and corrosion resistance of material mainly depends on the surface properties. Improved surface properties also increased the life span of components. The friction stir process is a novel solid-state processing technique that is widely used for welding difficult-to-weld materials. In this paper, the applications of the friction stir process in surface modificatio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
10
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 46 publications
(10 citation statements)
references
References 70 publications
0
10
0
Order By: Relevance
“…It is shown that FSP process parameters, such as rotational speed, transverse feed, number of passes, tool penetration depth, pin profiles and reinforcement volume fraction significantly influence the FSP process and play a vital role in the characteristic and mechanical properties of the fabricated composite. 17,23,[45][46][47][48] Many studies used threaded and square pin profiles, 47,49-51 800-1600 rpm for tool rotation speed, 27,50,52-54 40-160 mm/min for transverse feed. 27,[52][53][54][55] Table 3 shows the control parameters selected, and their corresponding levels for developing surface composite to achieve high UTS and minimum grain size.…”
Section: Methodsmentioning
confidence: 99%
“…It is shown that FSP process parameters, such as rotational speed, transverse feed, number of passes, tool penetration depth, pin profiles and reinforcement volume fraction significantly influence the FSP process and play a vital role in the characteristic and mechanical properties of the fabricated composite. 17,23,[45][46][47][48] Many studies used threaded and square pin profiles, 47,49-51 800-1600 rpm for tool rotation speed, 27,50,52-54 40-160 mm/min for transverse feed. 27,[52][53][54][55] Table 3 shows the control parameters selected, and their corresponding levels for developing surface composite to achieve high UTS and minimum grain size.…”
Section: Methodsmentioning
confidence: 99%
“…Type of reinforcement and processing parameters of FSP mostly influence the mechanical behaviour of the surface composite. Threaded pin profile of the FSP tool produced uniform distribution of reinforcement particles [17,18]. The microhardness of the surface composite 5A06Al/SiC was enhanced by 10% through the FSP technique [19].…”
Section: Introductionmentioning
confidence: 98%
“…Friction stir welding (FSW) is a solid-state joining process that uses a non-consumable tool to join two facing workpieces without melting the workpiece material 1 3 . The heat is generated by friction between the rotating tool and the workpiece material, which leads to a softened region near the FSW tool.…”
Section: Introductionmentioning
confidence: 99%